2014
DOI: 10.1007/s00216-014-8134-8
|View full text |Cite
|
Sign up to set email alerts
|

Nano-LC-MS/MS for the quantitation of prostanoids in immune cells

Abstract: Prostanoids, derivatives of arachidonic acid, are involved in inflammation and immune reactions. To understand the role of prostanoids produced by diverse immune cells, a highly sensitive quantitation method for prostaglandin E2 (PGE2), prostaglandin D2 (PGD2), 6-keto prostaglandin F1α (6-keto PGF1α), prostaglandin F2α (PGF2α), and thromboxane B2 (TXB2) by means of nano-liquid chromatography-tandem mass spectrometry has been developed. It was validated according to the guidelines of the Food and Drug Administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…An analysis of the samples was carried out using a nanoLC-MS/MS system, after the liquid-liquid extraction procedure (5500 QTrap, Sciex, Framingham, MA) (Thomas et al, 2014) (see Supplementary Methods for complete details).…”
Section: Prostanoid Measurementmentioning
confidence: 99%
“…An analysis of the samples was carried out using a nanoLC-MS/MS system, after the liquid-liquid extraction procedure (5500 QTrap, Sciex, Framingham, MA) (Thomas et al, 2014) (see Supplementary Methods for complete details).…”
Section: Prostanoid Measurementmentioning
confidence: 99%
“…19 In contrast, nano-LC-MS/MS method with C8 column has produced a reverse elution pattern for similar analytes with the elution order of TXB 2 , LTB 4 , PGF 2α , PGE 2 and PGD 2 . 21 After the generic screening, the method was further developed taking the effect of flow rates, backpressure and column temperature into account to improve the selectivity, sensitivity and the resolution of the AA-metabolites on the 2-PIC column. In general, higher retention time was observed with higher temperature while higher back pressure had opposite influence with little or no effects on resolution of isomers.…”
Section: Resultsmentioning
confidence: 99%
“…Our exploration focused on the extensively investigation of different solvents/ solvent mixtures including methanol, ethyl acetate, n-hexane : ethyl acetate (1 : 1 v/v), or hexane : isopropanol (1 : 1 v/v) and MTBE with spike plasma samples of AA-metabolites (30 ng mL −1 ). 7,21,24 Finally, methanol was selected as an extraction solvent based on the recovery % of each analyte. The mean recovery of analytes ranged from 70-115% on methanol (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Consequent studies revealed that although mast cells can generate leukotriene B4 (LTB 4 ), the cysteinyl leukotriene C4 (LTC 4 ) and PGD 2 upon activation, the specific profile or relative amounts of eicosanoid generation varies in both human and rodent mast cells depending on the tissue of origin, the stage of differentiation and culture conditions (Lundstrom et al, 2013) and reviewed in (Boyce, 2007). PGE 2 has not been considered to be an eicosanoid abundantly produced by antigen-stimulated mast cells in culture (Boyce, 2007) although a recent report detected higher intracellular content of PGE 2 than other prostanoids by mass spectrometry in mast cells isolated from inflamed tissue in a delayed type hypersensitive model (Thomas et al, 2014). Even though the release of eicosanoids by antigen-activated mast cells requires several enzymatic steps for their de novo production (Fig.…”
Section: - Eicosanoidsmentioning
confidence: 99%